Validity and Reliability of the Lithuanian Version of Prosocial Tendencies Measure – Revised (PTMR) (Baltic Journal of Sport and Health Sciences, 2015)
Background. The study was carried out with the aim to examine the construct validity and reliability of a Prosocial Tendencies Measure–Revised (PTM-R) (Carlo, Hausmann, Christiansen, & Randall, 2003). Methods. The  study  process  was  done  following  four  stages.  In  stage  1,  984  adolescents  between  ages  of 13 to 16 years (M age = 14.9, SD = 0.97; 50.3% girls) completed a translated version of the scale. In this stage Exploratory Factor Analyses (EFA) was carried out in order to measure the structure of the PTM-R. In stage 2, 757 adolescents between ages of 13 to 16 years (M age = 14.24, SD = .81; 51.78% girls) completed the questionnaire and Confirmatory Factor Analyses (CFA) was made. In stage 3, validity of the PTM-R was investigated. In stage 4, reliability of the measure was tested by evaluating Cronbach’s alpha values.Results.  Exploratory  Factor  analysis  of  the  PTM-R  revealed  four-factor  solutions. A  six-factor  solution  as in original measure was not obtained. Confirmatory factor analysis confirms four-factor structure of PTM-R and supports the multidimensional definition of prosocial behaviour. Three types of prosocial behaviour as anonymity, altruism, and public prosocial behaviour was the same as in the original measure. Other three types of prosocial behaviour emerged as one factor and were entitled as help in emergency. Correlation analyses between prosocial behaviour and different types of aggression showed good level of discriminant validity. Coefficient alpha was used to estimate of reliability based on the internal consistency among items. Alpha coefficients were .85 for help in emergency, .71 for anonymous prosocial behaviour, .68 for altruistic behaviour,  and .59 for public prosocial behaviour. Conclusions. In conclusion, the four-factor structure of PTM-R was obtained. Results showed that the adapted measure was valid and reliable for Lithuanian adolescents aged between 13 and 16. Contradiction to the original measure structure and future research directions are discussed.Keywords:  prosocial behaviour, prosocial behaviour measure, validity and reliability.